Methodological Approaches to the Assessment of the Innovative Urban Model - I. Pakhomova, Anna; Yu. Cherkesova, Elvira; I. Novikov, Andrey; A. Buryakov, Gennady; N. Goncharenko, Olga (International Journal of Psychosocial Rehabilitation, 2020)
The relevance of the research issue is due to the problems of development of Russian cities in the innovation economy. In this regard, this article aims at identifying the need to develop an innovative urban model. The leading approach to the study of this problem is a systematic method that allows a comprehensive study of the green economy in the modern city as a whole, as well as identifying the variety of cause-effect relationships occurring both within the system under study and in its interaction with the external environment. In this paper, the authors consider the green economy index, the city prosperity index, and their role in the formation of an innovative model of the city. The article presents an innovative model of a modern city and reveals the assessment methodology of urban development; the basic conditions for sustainable urban development are identified and justified. The materials of the article are of practical value for the authorities at the regional level in making management decisions on sustainable development of the region.